In silico Analysis of Plasmodium falciparum Actin and Profilin Interaction at the Interface Region for Antimalarial Drug Designing - Alam, Asrar; Kamal, Zahid; Fatima, Atiya (Letters in Drug Design & Discovery, 2015)
Malaria parasite Plasmodium falciparum actively invades its host cells utilizing its actin/ myosin-based motor machinery. Actin-profilin interaction is essential for actin filament dynamics in eukaryotic cells. P.falciparum profilin (PfPRF) is highly divergent from other eukaryotic profilins and possesses unique structural properties. In this study, we attempted to identify region(s) of P.falciparum actins (PfACT1 and PfACT2) that interact with unique region(s) of PfPRF at the binding interface. We identified nine-residue peptides from PfACT1 (PLNPKGNRE) and PfACT2 (PLNPKTNRE) that interacted with a unique region of PfPRF. This interaction was largely absent from docked human beta actin-human profilin 1 complex. By molecular docking, the peptide derived from PfACT1 bound at the unique region of the PfPRF interface. Virtual screening based on the peptide-binding region of PfPRF identified a number of drug-like molecules. Our study demonstrated that the unique region of PfPRF could be specifically targeted. Since actin polymerization is essential for parasite motility and invasion, inhibitors specifically targeting parasite actin-profilin interaction could be potential antimalarials.
Keywords: Virtual Screening